Transit Migration in Europe - Collyer, Michael; Duvell, Frank; Molodikova, Irina (IMISCOE Research, 2014)
Transit migration is a term that is used to describe mixed flows of different types of temporary migrants, including refugees and labor migrants. In the popular press, it is often confused with illegal or irregular migration and carries associations with human smuggling and organized crime. This volume addresses that confusion, and the uncertainty of terminology and analysis that underlies it, offering an evidence-based, comprehensive approach to defining and understanding transit migration in Europe.